The association between physical performance and match-play activities of field and assistants soccer referees. Issue 3 (3rd July 2019) - Castillo, Daniel; Cámara, Jesús; Lozano, Demetrio; Berzosa, César; Yanci, Javier
ABSTRACT: The aims of this study were to compare the external and internal match responses and fitness performance of national field referees (FRs) and assistant referees (ARs), and to examine the relationships between these fitness measures and physical and physiological responses during match play. Forty-four national soccer match officials (e.g. FRs and ARs) participated in this study. The distance covered and the VO2max in Yo-Yo Intermittent recovery test (YYIR1) and the 30 m sprint test correlated with high speed and high intensity activities during match play in FRs (r = −0.48–0.63, moderate to large, very likely to most likely, p < 0.05). In addition, YYIR1 performance was related to high accelerations (r = 0.41, moderate, likely, p < 0.05) and high decelerations (r = 0.44, moderate, very likely, p < 0.05) for FRs. Better sprint and cardiovascular fitness could be relevant to the performance of FRs during match play.